Assessment of knowledge and attitude on pharmacovigilance among the healthcare professional and pharmacy students at Dharan - Thapa, Shankar; Maharjan, Laxman; Karki, Badri; Pant, Lok Raj; Sharma, Badal Babu; Pariyar, Anil; Pariyar, Sujan (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Pharmacovigilance is the process of identifying, assigning, and reporting the adverse drug reaction (ADR) to prevent its possible effect of it. There are increasing cases of ADR in Nepal which is affecting the treatment protocol. This is due to the lack of knowledge and practice of pharmacovigilance-related activities. Method: It is a cross-sectional questionnaire-based study conducted among 105 healthcare professionals and pharmacy students at Dharan. Total 17 open and closed ended structured questions were provided to the participant. Out of 17 questions, 11 were ‘knowledge’ related and 6 were ‘attituded’ related. All the doctors, nurses, and pharmacists working in hospital and pharmacy premises during the data collection period were included. The response of the participant is analyzed by plotting the data on an excel sheet and the result is interpreted. Result: Almost 93.33% of participants gave a response and more than half of them (n=48; 54.54%) were female. Almost all the healthcare professionals 86.20% (n=50) were positive about establishing an ADR monitoring center in every hospital. Though the majority of respondent defined the term “pharmacovigilance”, less than half were aware the activities of national pharmacovigilance center. This shows that there is a need to address on the important of pharmacovigilance course at college level. The knowledge and attitude of respondents have shown difference with education qualification, age category, and profession category. Conclusion: Respondents had moderate to good knowledge about pharmacovigilance and had a positive attitude towards it. Most of them believe that the establishment of a pharmacovigilance center in each hospital is necessary.